Psychological symptoms and related risk factors among healthcare workers and medical students during the early phase of the COVID‐19 pandemic in Japan. Issue 1 (14th March 2022) - Tanifuji, Takaki; Aoyama, Shinsuke; Shinko, Yutaka; Mouri, Kentaro; Kim, Saehyeon; Satomi‐Kobayashi, Seimi; Shinohara, Masakazu; Kawano, Seiji; Sora, Ichiro
Abstract: Aim: The aim of this study was to investigate the mental health status of healthcare workers and medical students during the early phase of the COVID‐19 pandemic. Methods: An online questionnaire was administered to 637 students and 3189 healthcare workers from May to July, 2020. The patient healthcare questionnaire‐9 (PHQ‐9) and state anxiety (A‐State) of the state–trait anxiety inventory‐form (STAI) were used to assess depression and anxiety symptoms, respectively. Individuals were categorized into severe (15 or higher) depression and severe (50–51 or higher) anxiety groups. Results: Healthcare workers and those taking care of COVID‐19 patients had a higher risk of severe depression (PHQ‐9 scores >15) than other comparison groups. Students and men also had a higher risk of severe anxiety (STAI > 50–51). Multivariable logistic regression analysis showed that healthcare workers had a fivefold higher risk of developing severe depression symptoms (adjusted odds ratio [OR] = 4.99, confidence interval [CI] 2.24–5.97, P ‐value < 0.001) and those taking care of COVID‐19 patients had 2.8‐fold higher risk of developing severe depression symptoms (OR 2.75, CI 1.36–5.53, P ‐value = 0.005). Conclusion: Both medical students and healthcare workers have been experiencing depression and anxiety symptoms during the first wave of the pandemic. Our findings showed a high rate of severe anxiety symptoms in medical students and a high rate of severe depression symptoms in healthcare workers. Those who treated COVID‐19 patients were at greater risk of developing major depressive disorder than those who treated non‐COVID‐19 patients. Abstract : This study investigated the mental health status of healthcare workers and medical students during the early phase of the COVID‐19 pandemic. A high rate of severe anxiety symptoms in medical students and a high rate of severe depression symptoms in healthcare workers were found. Those who treated COVID‐19 patients were at greater risk of developing major depressive disorder than those who treated non‐COVID‐19 patients.